Creative Work in Hadith Studies in Ceuta and Its Impact in the East - Klaina, Mekki (Universitas Ahmad Dahlan, 2024)
This research examines creative work in Hadith studies in Ceuta due to its significance. Scholars in this region have been distinguished by their scholarly contributions, influencing others from different and being influenced by them as well. They introduced new areas in Hadith studies regarding book composition and refinement, similar to Al-Qadi 'Iyad in his book